Decomposing peer effects in pro-environmental behaviour: Evidence from a Chinese nationwide survey. (1st October 2021) - Wang, Bing; Zeng, Di; Yang, Bao
Abstract: We explore potential peer effects in pro-environmental behaviour using Chinese General Social Survey 2013, where individual participations in ten pro-environmental activities are recorded. Instrumental variable regressions suggest that individual pro-environmental behaviour is positively and significantly affected by that of neighbourhood peers. Such effects are robust against alternative estimation procedures and falsification tests. Results further show that, while identified peer effects do function through social networks, such mediation explains only a small portion of the peer effects, which may largely occur among strangers living in the neighbourhood through observation and mimicry. These findings imply that peer effects should be seriously considered in neighbourhood-level interventions to stimulate pro-environmental behaviour more cost-effectively. Highlights: We present a first evaluation of peer effects in pro-environmental behaviour in China. We provide evidence for endogenous effects, consistent and robust in all cases. We find social networks mediate only a small portion of the identified peer effects. We speculate neighbourhood observation or mimicry may be the main mechanism.